Thiol-reactive Passerini-methacrylates and Polymorphic Surface Functional Soft Matter Nanoparticles via Ethanolic RAFT Dispersion Polymerization and Post-polymerization Modification - Pei, Y.; Noy, J.; Roth, P.; Lowe, Andrew (R S C Publications, 2015)
RAFT dispersion polymerization (RAFTDP) is used to prepare reactive nanoparticles via the incorporation of Passerini-derived methacrylic comonomers containing pentafluorophenyl (PFP) groups. Copolymerization of 2-(dimethylamino)ethyl methacrylate with a Passerini comonomer gives copolymers suitable as macro-CTAs for ethanolic RAFTDP of 3-phenylpropyl methacrylate. Reaction of the PFP residues with functional thiols offers an approach for preparing surface modified nanoparticles.